INVESTIGATION OF THE INFLUENCE OF PARTICLE SIZE OF RICE HUSK ASH AS ADSORBENT FOR MERCURY IN COLUMN ADSORPTION SYSTEM - Desi Nurandini; Riani Ayu Lestari; Isna Syauqiah; Ahmad Rizalli; Ryan Rahmatullah (Konversi, 2021)
The presence of heavy metal mercury (Hg2+) in liquid waste has caused serious problems to environmental pollution. One of the most effective method to reduce the levels of heavy metals mercury (Hg2+) in liquid waste is adsorption. Rice husk ash is highly potential to adsorb heavy metals in water because it is a porous material with a high silica content. Therefore, rice husk ash can be used as an adsorbent for heavy metals in liquid waste. The purpose of this study was to determine the level of mercury (Hg2+) that can be adsorbed from the column adsorption process using adsorbent of rice husk ash and to determine the optimum mass of rice husk ash as an adsorbent. The research was conducted using a series of simple adsorption column tools with a circulation time of 120 minutes. While the independent variables were adsorbent particle size of 50, 100, and 200 mesh. Measurement of mercury (Hg2+) levels was carried out on samples before and after treatment with Atomic Absorption Spectrophotometer (AAS). The results showed a significant decrease in Hg2+ levels with the optimum adsorbent particle size of 200 mesh. The value of the adsorbed Hg2+ ion content reached 101.670 mg/L in the adsorption process using adsorbent with 200 mesh particle size .